A supramolecular bactericidal material for preventing and treating plant-associated biofilms - Jinghan Yang; Kongjun Liu; Yazhen Chen; Haojie Ye; Gefei Hao; Fengpei Du; Peiyi Wang (Nature Communications)
Abstract Treating bacterial biofilms on plants poses challenges due to biofilm induced resistance and poor agent adhesion on plant leaves. Here, we report on a host-guest self-assembled material which is biocompatible, has a lamellar supramolecular structure for leaf retention and prevents and treats bacterial biofilms. Phosphate/isopropanolamine-modified ferrocene forms a host-guest complex with β-CD which assembles into a lamella structure. The agent shows control efficacy against bacterial blight, bacterial leaf streak, and citrus canker in testing.